CANCER Patients and their Emotions – Negative Or Positive? (or in any Acute or Chronic diseased conditions.) (Advancements in Homeopathic Research, 2022)
“Life is like riding a bicycle. To keep your balance you must keep moving”. (Einstein ). Our body is the finest. It is genuine fact that our body and mind experiences all pleasures, sorrows and pains. Our body, mind and Soul(Spirit) - (Trinity) are working together and capable of defending our health. Defence by body, mind, and Soul are our immunity. Positiveness is our immunity. Immunity is a defence against disease or diseases; may be acute or chronic or cancer. If we are more positive and happy, stronger is our immunity. Health is a state of harmony in body, mind, and Soul(Spirit). Disease is a state of disharmony of body and mind and soul(spirit). We have usually two types of emotions. One is positive and the other one is negative. There is an another one which is beyond these two, The Divine. You call it conscience or spiritual or will power or vital power(Force) or vitality (The Principal of Life) or dynamic force, or Soul or any thing you may call it but that is there in every individual human being. Conscience is of prime importance in health and diseases. If that level you are sick you can be mostly doing some thing wrong in your life without knowing what you have done and why you are doing. This is followed by Will and then emotions, intellect, memory.
Keywords: CANCER Patients; Emotions; weakness